The Impact of 9-Valent HPV Vaccination on Couple Infertility Prevention: A Comprehensive Review - Ciavattini, Andrea; Marconi, Chiara; Giannella, Luca; Delli Carpini, Giovanni; Sopracordevole, Francesco; Di Giuseppe, Jacopo (Frontiers in Medicine, 2021)
A comprehensive literature review was performed to determine the relationship between HPV infection and infertility and the eventually role of 9-valent vaccine for infertility prevention. The search was extended from January 1997 through July 2021. Data collected from selected articles were focused on three main topics: statistical associations between HPV prevalence and assisted reproductive technology (ART) outcome, association between HPV and characteristics of semen, and associations between HPV and miscarriage. Articles that identified HPV genotypes were selected for this review to study the possible role of 9-valent vaccine in infertility prevention. To date, there is no agreement on implication HPV female infection has on the fertility and miscarriage rate. Although it can be stated that HPV prevalence among couples with infertility undergoing ART treatment is consistent, it does not seem to affect oocyte’s performance. Otherwise, HPV infection affects sperm parameters, in particular spermatozoa motility. When an association can be found, most HR- HPV involved are those included in 9-valent vaccine. The correlation between HPV male infection both with asthenozoospermia and increased risk of pregnancy loss could make recommendable the extension of anti-HPV vaccination to adolescent males, along with cancer prevention. Despite the relation between 9-valent HPV genotypes involved in female infection and miscarriage/infertility is not clear, the impact of this virus on health reproduction is evident. Considering this, the importance of HPV vaccination in adolescent females is confirmed. A vaccine efficacy study could be useful to confirm the importance of primary prevention for couple reproductive health.